Evaluation of stability of mini implants as bony anchorage for upper molar intrusion - Arismendi-E., Jorge A.; Ocampo-A., Zandra M.; Morales-B., Marcela; González-C., Francisco J.; Jaramillo-V., Pedro M.; Sánchez-U., Alejandro (Revista Facultad de Odontología Universidad de Antioquia, 2009)
The aim of this study was to undertake a clinical stability evaluation of the mini implant used as bony anchorage for the intrusion of upper molars. Thirty four Leone® stainless steel mini implants were used (four dimensions: 1.5 x 10 mm, 1.5 x 12 mm, 2 x 10 mm and 2 x 12 mm), in nine patients and a total of 18 teeth to be intruded. The insertion procedure was performed according to the manufacturer’s recommendations. The stability of the mini implants was evaluated monthly measuring its clinical mobility by means of a digital Boley gauge. It was found that all the mini implants placed were effective as bony anchorage to carry out the intrusive movement in spite of the appearance of mobility in some of them, which is an indication that mini implants can have certain range of movement without losing its clinical effectiveness. It was found that variables such as the force applied to the mini implant, the dimension (length and diameter) and the insertion torque are not related to stability. Conversely, it was found that mini implants located in the palatal mucosa were more stable than those located in the vestibular area. The keratinized gingiva presents better clinical conditions (less inflammation and hyperplasia) than the alveolar mucosa for the mini implant placement because it favors stability throughout time. No signs of root resorption in any of the molars were found in the radiographic evaluation.